Uncertain predictive value of traditional diagnosis for femoroacetabular impingement in young people. Is this a pure pathology or a morphological and functional sneaky feature? - Petruccelli, Rosario; Manfreda, Francesco; Di Giacomo, Lorenzo Maria; Ceccarini, Paolo; Caraffa, Auro; Antinolfi, Pierluigi (Lo Scalpello - Journal, 2022)
Femoroacetabular impingement (FAI) is a pathological condition with an underestimated prevalence both in general adult population and in young and sportive people. Predisposing factors are still not clear, but it seems related to a previous pathology leading to hip osteoarthritis. Considering FAI as a pure anatomical dysfunction it could be absolutely reductive. Symptoms seem to be linked to a late onset of clinical presentation of damage to histological and anatomical structures of the hip joint, both in femoral and in pelvis portions. Anatomical features can vary and mixed between several forms of alterations. Clinicians and physicians should conduct their studies in an early approach to discover prior signs of anatomical and functional sneaky features that occur prior to symptoms. In the literature, the use of classical and well known clinical and radiological tests has been demonstrated to lead to a late diagnosis; it is also linked to a poor sensitivity. Arthro-MRI has been proposed as an innovative thorough method to properly evaluate the anatomical pattern, but recognized targets and methodology are still missing. In addition, this does not underline the functional patterns and dysfunction, characteristic of young people suffering from this clinical entity. Biomechanical evaluation, both in kinematic and in kinetic studies, may represent a correct means to evaluate people with pathological family history or predisposing factors to discover the early features of FAI and hypothesize treatment and prevention pathways.